United Arab Emirates : Selected Issues. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2015)
This Selected Issues paper discusses measures to strengthen fiscal policy and budget frameworks in the United Arab Emirates (UAE). It provides an overview of government's revenue and expenditure developments, and presents fiscal sustainability analysis that is most relevant to countries with large hydrocarbon wealth such as the UAE. The paper discusses measures to contain expenditure growth-controlling the public wage bill, reducing subsidies and transfers, and stabilizing other expense in real terms. It also proposes options to increase nonhydrocarbon revenue such as broadening corporate income tax with lower rates, introducing a low rate-broad based value added tax, and levying an excise tax on automobiles.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet